1988
DOI: 10.1200/jco.1988.6.9.1474
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases in adenocarcinoma of the lung: frequency, risk groups, and prognosis.

Abstract: A consecutive group of 259 patients with inoperable adenocarcinoma of the lung (ACL) were observed to define risk groups for and frequency of brain metastases together with prognosis. All patients received chemotherapy in a three-armed randomized trial. Brain metastases were diagnosed in 25 patients before protocol entry and in 37 during treatment. Brain autopsy was performed in 87 patients and was positive in 38 (44%). Eleven of these (29%) were not diagnosed clinically. Patients younger than 60 years had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
186
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(194 citation statements)
references
References 19 publications
7
186
1
Order By: Relevance
“…The internal mechanism of this distribution remains unknown. Primary lung cancer frequently metastasizes to bone as well as brain 28, 29, 30, 31. Some studies had suggested that there was cross‐talk among lung tumor cells, bone microenvironment, and immune system, which led to bone metastasis formation in primary non‐small cell lung cancer patients 32.…”
Section: Discussionmentioning
confidence: 99%
“…The internal mechanism of this distribution remains unknown. Primary lung cancer frequently metastasizes to bone as well as brain 28, 29, 30, 31. Some studies had suggested that there was cross‐talk among lung tumor cells, bone microenvironment, and immune system, which led to bone metastasis formation in primary non‐small cell lung cancer patients 32.…”
Section: Discussionmentioning
confidence: 99%
“…10 In lung cancer, brain metastases are common with about 10% of patients presenting with small-cell lung cancer having brain metastases and rising to B40% at autopsy. 11 Other cancers metastasizing to the brain include breast with 10-20% of patients, 12 followed by renal and colorectal. 13 The percentage of patients where their primary tumor metastasizes to the brain has been increasing over the last two decades, related in part to the increased efficacy of current treatments for primary disease and the associated increased survival.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Approximately 10%-20% of patients present with synchronous brain metastases at the time of diagnosis, and the optimal treatment strategy for this group of patients remains poorly defined. Some reports suggest that survival is worse in patients presenting with a synchronous BM from NSCLC, as opposed to a metachronous presentation.…”
mentioning
confidence: 99%